CROYANCES COLLECTIVES ET DISCONTINUITE DU SUIVI PRENATAL EN MILIEU URBAIN IVOIRIEN (ABIDJAN / COTE D’IVOIRE) - Hendersonn, N’guessan Kouame (European Scientific Journal, ESJ, 2015)
Antenatal care (ANC) is an activity allowing the medical care of pregnant women so as to prevent possible complications with pregnancy and birth, which may cause diseases to the extent of the death of the mother. However, that activity is irregularly carried out by pregnant women in the Ivorian urban environment, while they are subject to important stimulus affecting attitude. In view of that situation, the present study is to analyze the influence that has the level of knowledgeof antenatal care components on compliance with said components in pregnant women (analyzes of 1st trimester, prenatal visits and ultrasounds). Therefore, an indirectly administrated questionnaire was administered to a sample of one thousand three hundred and fifty two (1,352) women from seven (7) to nine (9) months of pregnancy selected on the basis of antenatal consultations statistics in seven (7) governmental general hospitals. Data were analyzed using the chi square of Pearson. It results that the discontinuity in antenatal care, perceptible through the realization of tests prescribed during the first antenatal visit, regular antenatal visits and ultrasounds checks is related to collective beliefs elaborated based upon the level of knowledge about prenatal care components.